Self-Organizing Architecture for Information Fusion in Distributed Sensor Networks. (29th March 2015) - Bajo, Javier; De Paz, Juan F.; Villarrubia, Gabriel; Corchado, Juan M.
Abstract : The management of heterogeneous distributed sensor networks requires new solutions that can address the problem of automatically fusing the information coming from different sources in an efficient and effective manner. In the literature it is possible to find different types of data fusion and information fusion techniques in use today, but it is still a challenge to obtain systems that allow the automation or semiautomation of information processing and fusion. In this paper, we present a multiagent system that based on the organizational theory proposes a new model to automatically process and fuse information in heterogeneous distributed sensor networks. The proposed architecture is applied to a case study for indoor location where information is taken from different heterogeneous sensors.